2021
DOI: 10.1596/1813-9450-9511
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Public Procurement Regimes, and Trade Policy

Abstract: This paper analyzes a prominent dimension of the initial policy response to the COVID-19 pandemic observed in many countries: the imposition of export restrictions and actions to facilitate imports. Using weekly data on the use of trade policy instruments during the first seven months of the COVID-19 pandemic (January-July, 2020) we assess the relationship between the use of trade policy instruments and attributes of pre-crisis public procurement regulation. Controlling for country size, government effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…The data set permits analysis of compliance with-and the effects of-applicable trade agreements. An example of such research is Hoekman et al (2021), who investigate the relationship between the use of trade policy observed in the first 6 months of the pandemic and characteristics of national public procurement regimes, including membership of the WTO Agreement on Government Procurement and deep trade agreements that include provisions on public procurement. They find statistically strong associations between characteristics of public procurement regimes and the use of trade policy by countries.…”
Section: Compatibility With Wto Rules and Trade Agreement Commitmentsmentioning
confidence: 99%
“…The data set permits analysis of compliance with-and the effects of-applicable trade agreements. An example of such research is Hoekman et al (2021), who investigate the relationship between the use of trade policy observed in the first 6 months of the pandemic and characteristics of national public procurement regimes, including membership of the WTO Agreement on Government Procurement and deep trade agreements that include provisions on public procurement. They find statistically strong associations between characteristics of public procurement regimes and the use of trade policy by countries.…”
Section: Compatibility With Wto Rules and Trade Agreement Commitmentsmentioning
confidence: 99%
“…As data handling becomes difficult each day due to rapid development in the internet databases, enterprises find it difficult to manage their data regarding exports and imports. In other words, the data/information of trading is inseparable from internet databases ( 7 , 26 , 27 ). To make appropriate use of resources and as a part of economic globalization, organizations utilize big data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Examining data using big data technology is considered scientific, logical, and perfect in nature, when compared with traditional enterprise management ( 9 , 12 , 13 ). To improve the quality of a business, SMEs make use of big data to make an accurate and quick decisions in the need of the hour ( 7 , 27 ). The literature review shows that the use of big data in the business will enhance the whole process of business, and for this reason, SMEs are considering adopting big data to businesses ( 12 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On average, producers in Africa have to wait six months to receive payments from public contracts (World Bank, 2016) Investment in e-procurement systems can improve timely and transparent payments of suppliers. The use of e-procurement systems stands at less than 25% for most African countries, compared to more than 75% for member states of the European Union and the Association of Southeast Asian Nations (Hoekman et al, 2021). In Cabo Verde, the institutional reform and new e-procurement system encouraged the participation of small and medium-sized enterprises in the bidding processes, from only 15 enterprises in 2012 to 444 in 2015, and stimulated average growth in sales revenue by 43% (World Bank, 2016).…”
Section: Modernising and Broadening Public Procurement Programmes Wil...mentioning
confidence: 99%